2017
DOI: 10.18632/oncotarget.14926
|View full text |Cite
|
Sign up to set email alerts
|

Detection fidelity of AR mutations in plasma derived cell-free DNA

Abstract: Somatic genetic alterations including copy number and point mutations in the androgen receptor (AR) are associated with resistance to therapies targeting the androgen/AR axis in patients with metastatic castration resistant prostate cancer (mCRPC). Due to limitations associated with biopsying metastatic lesions, plasma derived cell-free DNA (cfDNA) is increasingly being used as substrate for genetic testing. AR mutations detected by deep next generation sequencing (NGS) of cfDNA from patients with mCRPC have b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The importance of suitable enzymes, i.e. proofreading DNA-polymerases (containing 3′ → 5′ exonuclease activity) for high-fidelity requirements like the amplification for high-throughput sequencing and rare mutation detection, confirms previous reports [ 24 , 25 ]. Due to its particular relevance as the most frequent somatic change in myeloproliferative neoplasms [ 26 ], several assays (mainly qPCR-based) have already been described for the detection of JAK2 p.Val617Phe with only some achieving a sufficient sensitivity for MRD detection [ [27] , [28] , [29] , [30] , [31] , [32] ].…”
Section: Discussionsupporting
confidence: 84%
“…The importance of suitable enzymes, i.e. proofreading DNA-polymerases (containing 3′ → 5′ exonuclease activity) for high-fidelity requirements like the amplification for high-throughput sequencing and rare mutation detection, confirms previous reports [ 24 , 25 ]. Due to its particular relevance as the most frequent somatic change in myeloproliferative neoplasms [ 26 ], several assays (mainly qPCR-based) have already been described for the detection of JAK2 p.Val617Phe with only some achieving a sufficient sensitivity for MRD detection [ [27] , [28] , [29] , [30] , [31] , [32] ].…”
Section: Discussionsupporting
confidence: 84%
“…By contrast, Goldstein et al . showed that cfDNA mutation detection in prostate cancers by NGS in the androgen receptor axis may lead to false positive cases that are not observed with ddPCR assays [ 22 ]. This highlighted the importance of setting the proper clinical cut-off values specific for the platform being used to detect mutations in cfDNA with particular attention to establishing margins of security that are assay-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, we detected D538G in 24.5% of our prostate cancer samples. To contrast with other hormone receptors investigated in men with advanced prostate cancer, reported AR mutations range from 8.2% to 45%, where they have been associated with poor outcomes . In the present study we used RNA samples derived from blood as an indirect measure of cfRNA and, in turn, circulating tumour RNA, to identify somatic mutations associated with prostate cancer and to analyse RNA splice variants.…”
Section: Discussionmentioning
confidence: 99%